1990
DOI: 10.1002/1097-0142(19900201)65:3<425::aid-cncr2820650309>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant portal liver infusion in colorectal cancer with 5-fluorouracil/heparin versus urokinase versus control results of a prospective randomized clinical trial (colorectal adenocarcinoma trial I)

Abstract: This prospectively randomized clinical trial was carried out in four Dutch hospitals to reduce the development of metachronous liver metastases and to get a better survival in patients with colorectal malignancies after surgically radical en bloc resection of the primary tumor and the regional lymph nodes. Three hundred seventeen patients were randomized to participate in three trial arms. One group of patients was treated by surgery alone (control group); in the other patients a catheter was placed in the dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…In the adjuvant setting of colorectal cancer patients, Wereldsma et al reported in a controlled, randomised trial a reduced risk to develop liver metastases in the 5-FU/heparin group compared to surgery alone or intra-portal infusion of urokinase for 24 h (P < 0.01) [79]. Similar results have been reported by Fielding et al [80].…”
Section: Anticoagulation and Prognosis Of Cancermentioning
confidence: 99%
“…In the adjuvant setting of colorectal cancer patients, Wereldsma et al reported in a controlled, randomised trial a reduced risk to develop liver metastases in the 5-FU/heparin group compared to surgery alone or intra-portal infusion of urokinase for 24 h (P < 0.01) [79]. Similar results have been reported by Fielding et al [80].…”
Section: Anticoagulation and Prognosis Of Cancermentioning
confidence: 99%
“…These findings are comparable to the results of some clinical trials which have shown a decrease in the number of hepatic recurrences in i.port. treated groups (Taylor et al, 1985;Wereldsma et al, 1990) compared to control groups, but which did not include i.v. treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regional post-operative adjuvant therapy via the portal vein could be an effective means of preventing the development of liver metastases, by delivering higher local drug concentrations to tumour cells at the onset of metastatic invasion. Several clinical trials have been designed to test this hypothesis (Taylor et al, 1985;Gray et al, 1987;Ryan et al, 1988;Wolmark et al, 1990;Metzger et al, 1990;Wereldsma et al, 1990;Beart et al, 1990;Fielding et al, 1992). Most of them used 5-FU alone, or in association with mitomycin C in different schedules.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Esto hizo que fuera la vía portal la que se empleó con más asiduidad para los primeros tratamientos locorregionales. Este es un procedimiento de cierta complejidad técnica y se ensayó tras resección de tumores primarios en un buen número de ensayos [2][3][4][5][6][7][8] . Aunque en alguno de ellos se detectó un aumento en la supervivencia, en el mayor de ellos 7 fue sin mejorar el control hepático, por lo que se atribuyó su efecto al paso sistémico de la droga.…”
unclassified